Zincothermic reduction of silica to silicon: make the impossible possible. Issue 37 (8th September 2021) - Cai, Muya; Zhao, Zhuqing; Qu, Jiakang; Ma, Qiang; Qu, Xin; Guo, Lei; Xie, Hongwei; Wang, Dihua; Yin, Huayi
Abstract : Schematic illustrations of both thermodynamic and kinetic considerations of the zincothermic reduction of SiO2 assisted by AlCl3 . Abstract : Metallothermically reducing silica to nano-silicon is an energy-effective and straightforward way using low-cost raw materials. Herein, we report a scalable technique to produce nano-Si particles from SiO2 with the assistance of AlCl3, using zinc (Zn) as the reductant, and Zn can be recovered by electrochemical deposition in an aqueous solution. Thermodynamically, the reactivity of metal reductants should be higher than that of Si. However, opposing the thermodynamic rule, SiO2 can be reduced to Si by Zn that is less reactive than Si. The underlying mechanism of the abnormal spontaneous zincothermic reduction reaction stems from the existence of AlCl3 acting as a chlorination agent that first transforms SiO2 into SiCl4, which is subsequently reduced by Zn. Thus, the reaction of AlCl3 -assisted metallothermic reduction of SiO2 is herein revealed for the first time, which is termed the chlorination–reduction reaction that obeys the thermodynamic rule. The revealed chlorination–reduction mechanism can explain the reason why the AlCl3 additive can enable the metallothermic reduction of SiO2 at such a low temperature of 250 °C. Moreover, the obtained nano-Si delivers a specific discharge capacity of 1450 mA h g −1 at 2 A g −1 after 400 cycles. Overall, this paper expands the choice of reductants and provides new insights into understanding the AlCl3 -assisted metallothermic reduction of SiO2 .